Tephra-stratigraphy and Ash Componentry Studies of Proximal Volcanic Products at Mount Tangkuban Parahu, Indonesia: An Insight to Holocene Volcanic Activity - Angkasa, Syahreza S.; Ohba, Tsukasa; Imura, Takumi; Setiawan, Iwan; Rosana, Mega (Indonesian Journal on Geoscience, 2019)
DOI: 10.17014/ijog.6.3.235-253Tangkuban Parahu Volcano is one of the most active volcanoes in West Java, Indonesia, although most of the recent eruptions were relatively mild (e.g. 2013 eruption). However, there is still little information from the volcanic products in the proximal area. Here, a new documentation from the proximal volcanic succession is provided, including tephra-stratigraphy, componentry analysis, and petrography of volcanic products. Detailed mapping of the proximal area shows that the volcanic products are predominantly composed of alternating fine-clay and coarse ash, lapilli tuff, and pyroclastic breccia within ten tephra units. Componentry of ash particles revealed the presence of five components, associated with hydrothermally altered lithics, oxidized lithics, coherent crystalline lithics, magmatic juvenile, and free crystal in entire eruptive products. These indicate that the subvolcanic hydrothermal system has been developed since the Holocene and associated with a continual introduction of magmatic intrusion. Petrographic observation shows the presence of hydrothermal minerals of quartz or silica accompanied by alunite and kaolinite, representing acidic alteration within the crater-conduit. The existence of a silicified zone indicates that the subvolcanic hydrothermal system played an essential role as a cap-rock of pressurized gas and steam at depth (200-500 m), whereas magmatic injection caused the vapour plume expansion. The observation concluded that the proximal volcanic succession captured the evidence of coupled phreatic and phreatomagmatic activities during the latest development of Mount Tangkuban Parahu.